The Prognostic Significance of a Cast Fourth Ventricle in Ruptured Aneurysm Patients With Intraventricular Hemorrhage in the Barrow Ruptured Aneurysm Trial (BRAT). Issue 2 (23rd November 2018) - Catapano, Joshua S; Zabramski, Joseph M; Baranoski, Jacob F; Brigeman, Scott; Morgan, Clinton D; Hendricks, Benjamin K; Mooney, Michael A; Albuquerque, Felipe C; Nakaji, Peter; Spetzler, Robert F
Abstract: BACKGROUND: Ruptured aneurysms causing intraventricular hemorrhage (IVH) are associated with high morbidity. The presence of blood that completely fills the fourth ventricle (cast fourth ventricle, CFV) is thought to be particularly ominous, but studies documenting the outcome of such cases are lacking. OBJECTIVE: To investigate the outcomes of patients with aneurysmal subarachnoid hemorrhage (aSAH) and CFV. METHODS: We reviewed 406 patients enrolled in the Barrow Ruptured Aneurysm Trial (BRAT, NCT01593267, clinicaltrials.gov); 238 patients with aSAH and IVH were identified, and imaging was reviewed for the presence of CFV. Outcome was evaluated at the 1-yr follow-up. A poor outcome was defined as modified Rankin Scale score >2. RESULTS: CFV was identified in 25 patients. Admission Glasgow Coma Score was lower in CFV patients, 7.8 versus 11.5 ( P < .001). At discharge and the 1-yr follow-up, patients with CFV had a greater risk of a poor outcome ( P < .001 and P = .002, respectively). In a subgroup analysis of 79 patients with IVH and initial Glasgow Coma Score ≤ 8, almost 50% of the patients with IVH but without CFV had made a good recovery versus 7% of patients with CFV (odds ratio [OR] 15, P = .002). On multivariate analysis, CFV was a greater predictor of a poor prognosis at 1 yr post-aSAH than Hunt and Hess grade >3 (6.4 OR vs 2.9 OR [ P < .001], respectively). CONCLUSION: The presence of CFV is a predictor of poor outcome in patients with aSAH. When compared to other patients with IVH and aSAH, CFV is a stronger predictor of a poor outcome than a poor Hunt and Hess Grade.